S50 Airway Smooth Muscle Inflammation Is Controlled By Microrna-145 Targeting Of Smad3 In Copd. (10th November 2014) - O'Leary, L; Tildy, B; Papazoglou, E; Adcock, IM; Chung, KF; Perry, MM
Abstract : Introduction and objectives: Airway smooth muscle cells (ASMCs) may contribute to the pathological airway inflammation and remodelling in COPD through the secretion of inflammatory cytokines and increased proliferation. Our previous work demonstrated that ASMCs from patients with COPD release greater amounts of IL-6 and CXCL8 compared to those from healthy subjects and are in a state of hyperproliferation. MicroRNAs (miRNAs) have recently emerged as important homeostatic regulatory molecules in COPD, and we have previously demonstrated the role of these in controlling ASMC proliferation in asthma. We hypothesise that microRNA-145 (miR-145) controls the aberrant phenotype observed in ASMCs from patients with COPD by targeting SMAD3, an important downstream signalling molecule of the TGF-β pathway. Methods: Human primary ASMCs were grown from individuals classified as being healthy non-smokers, healthy smokers, or those with COPD (n = 9 per group). Cells were stimulated with TGF-β and foetal calf serum, and miRNA and mRNA expression levels were measured by RT-PCR. IL-6 and CXCL8 release was measured by ELISA. Transfection of miR-145 mimics and inhibitors were used to model the effects of miR-145 over-expression and knock-down, respectively. Results: Low concentrations of TGF-β significantly upregulated SMAD3 expression in ASMCs from patients with COPD. Higher concentrations of TGF-β led to a suppression of SMAD3 expression, with a concomitant increase in miR-145 expression in these cells, to a greater degree than in healthy subjects. Inhibiting miR-145 in ASMCs from COPD patients reduced the increased IL-6 and CXCL8 release and proliferation back to levels comparable to that of healthy individuals. Conclusions: This is the first time that miR-145 has been demonstrated to be important in controlling the increased inflammatory state of ASM cells from COPD patients. This miRNA may not only act as a novel biomarker for COPD, but may also be a novel target for treatment.